ANALYSIS OF OVERPRESSURE GENERATION AND PORE PRESSURE ESTIMATION, SANGATTA FIELD, LOWER KUTAI BASIN - (NIM: 22014039), ARFIZALDI
The study area is located in Sangatta, The Lower Kutai Basin, East Kalimantan. The topics in this study are overpressure characteristics, the cause of overpressure, and pore pressure estimation. The data used in this study are wireline log, well-drilling report, formation pressure, vitrinite reflectance and geotemperature. Based on wireline log and pore pressure pattern, it is found that all wells penetrated overpressure zone.The tops of overpressure are located in claystone dominated lithology. The tops of overpressure in three wells are located in Pulubalang Formation and only in one well that top of overpressure is located in Balikpapan Formation. It can therefore be concluded that tops of overpressure cross stratigraphic unit, and they depend on the presence of claystone dominated lithology. The result of the analysis also reveals that the cause of overpressure in the study area is non-loading mechanism. The integrated analysis of XRD and SEM was performed to know clay mineral diagenesis in the study area. The result of XRD and SEM analysis shows that there is no indication of clay mineral diagenesis in forms of illitization of smectite. The analysis of source rock maturation was obtained from the review of previous study and maturation modelling. The result shows that top of source rock maturation in Pinang 1 well coincides with top of overpressure, and the result of maturation modelling of SD-1 well also shows the similar condition. Therefore, it can be concluded that the mechanism responsible for non-loading overpressuring in the study area is source rock maturation. Pore pressure estimation by Eaton Method can match with mud weight used during drilling. The Eaton's exponent used in the calculation is in the range of 1.5 to 2.2.